Susceptibility of carbapenem-resistant Klebsiella pneumoniae in urinary tract infections: clinical efficacy of fosfomycin - Kaya, Arda; Akyol-Seyhan, Deniz; Chousein-Memetali, Seichan; Yaşar, Melike; Mert-Vahabi, Merve; Başkol-Elik, Dilşah; Dirik, Şükrü; Şanlıdağ-İşbilen, Gamze; Bulut-Avşar, Cansu; Demir-Görür, Melike; Guliyeva, Gunel; Uyan-Önal, Ayşe; et al. (The Journal of Infection in Developing Countries, 2026)
Introduction: The increasing prevalence of carbapenem-resistant Klebsiella pneumoniae (CR-Kp) limits effective treatment options. The aim of this study was to evaluate the susceptibility patterns of CR-Kp strains isolated from urine cultures to oral treatment options recommended by the Infectious Diseases Society of America guidelines, and ceftazidime-avibactam. Additionally, clinical data and outcomes of patients diagnosed with CR-Kp urinary tract infections (UTI) who were treated with fosfomycin sodium-including therapy regimens (FSITR) were analyzed. Methodology: This retrospective cohort study included adult patients with urine culture-proven CR-Kp between March 2016 and October 2022. Demographic and clinical data, antibiotic susceptibility, treatment outcomes, and one-month mortality (OMM) were evaluated. Results: A total of 179 patients were included. The susceptibility to fosfomycin tromethamol, nitrofurantoin, and co-trimoxazole (TMP-SMX) were (33.7%; 55/163), (7.7%; 13/167), and (11.1%; 20/179), respectively. All strains were resistant to ciprofloxacin. The susceptibility data compared until 2020 (pre-COVID-19) and afterwards, revealed TMP-SMX susceptibility (4.9% vs 24.1%, p = 0.0001) increased significantly. Susceptibility data for ceftazidime-avibactam were available for 22 isolates and 59% of the isolates were sensitive. OMM of the 179 patients with CR-Kp in urine cultures was 37.4% (67/179). There were 9 FSITR cases. Among those, microbiological eradication was achieved in 87.5% (7/8) and OMM was 44.4% (4/9). Conclusions: Clinical experience may be feasible and needed to assess the efficacy of nitrofurantoin and TMP-SMX. Fosfomycin-including regimens may serve as a salvage treatment option for CR-Kp UTI in selected patients. However, the retrospective and single-center design of the study should be considered as a limitation.